Profitability Identification of National Banking Through Credit, Capital, Capital Structure, Efficiency, and Risk Level - Haryanto, Sugeng (Jurnal Dinamika Manajemen, 2016)
This study aims to analyze the influence of credit, bank capital, capital structure, efficiency and risk toward the profitability in banking industry. Bank has an important role in the economy in Indonesia in 2014. The purposive sampling technique was used in this study to filter the samples according to several criteria such as being public at least in 2008, and publicly released the financial statement from 2008-2013. The total sample of 25 banks. Multiple regression technique was used in this study to analyze the data. The results show that credit, bank capital, and capital structure positively influence the profitability. This result supported by the previous research. The other finding shows that efficiency and risk have significantly negative effect on profitability. Bangking has an 80 percent market share in the financing of intermediation function of the entire financial system.Penelitian bertujuan menganalisis pengaruh antara kredit, permodalan bank, struktur modal, efisiensi dan risiko terhadap profitabilitas pada industri perbankan. Bank mempunyai peran penting dalam ekonomi Indonesia 2014. Teknik sampling penelitian ini adalah purposive sampling, dengan kriteria bank bank telah go public sebelum tahun 2008, mempublikasikan laporan keuangan tahun 2008-2013. Jumlah sampel sebanyak 25 bank. Teknik analisis yang digunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa kredit, permodalan bank dan struktur modal berpengaruh terhadap profitabilitas dengan arah positif. Hasil lainnya adalah variabel efisiensi dan risiko berpengaruh signifikan dengan arah negatif terhadap profitabilitas. Perbankan memiliki market share 80 persen dalam sistem keuangan.JEL Classification: G3, G32